Cannabidiol prevents methamphetamine-induced neurotoxicity by modulating dopamine receptor D1-mediated calcium-dependent phosphorylation of methyl-CpG-binding protein 2 - Shen, Baoyu; Zhang, Ruilin; Yang, Genmeng; Peng, Yanxia; Nie, Qianyun; Yu, Hao; Dong, Wenjuan; Chen, Bingzheng; Song, Chunhui; Tian, Yan; Qin, Lixiang; Shu, Junjie; et al. (Frontiers in Pharmacology, 2022)
In the past decade, methamphetamine (METH) abuse has sharply increased in the USA, East Asia, and Southeast Asia. METH abuse not only leads to serious drug dependence, but also produces irreversible neurotoxicity. Currently, there are no approved pharmacotherapies for the treatment of METH use disorders. Cannabidiol (CBD), a major non-psychoactive (and non-addictive) cannabinoid from the cannabis plant, shows neuroprotective, antioxidative, and anti-inflammatory properties under METH exposure. At present, however, the mechanisms underlying these properties remain unclear, which continues to hinder research on its therapeutic potential. In the current study, computational simulations showed that CBD and METH may directly bind to the dopamine receptor D1 (DRD1) via two overlapping binding sites. Moreover, CBD may compete with METH for the PHE-313 binding site. We also found that METH robustly induced apoptosis with activation of the caspase-8/caspase-3 cascade in-vitro and in-vivo, while CBD pretreatment prevented these changes. Furthermore, METH increased the expression of DRD1, phosphorylation of Methyl-CpG-binding protein 2 (MeCP2) at serine 421 (Ser421), and level of intracellular Ca2+ in-vitro and in-vivo, but these effects were blocked by CBD pretreatment. The DRD1 antagonist SCH23390 significantly prevented METH-induced apoptosis, MeCP2 phosphorylation, and Ca2+ overload in-vitro. In contrast, the DRD1 agonist SKF81297 markedly increased apoptosis, MeCP2 phosphorylation, and Ca2+ overload, which were blocked by CBD pretreatment in-vitro. These results indicate that CBD prevents METH-induced neurotoxicity by modulating DRD1-mediated phosphorylation of MeCP2 and Ca2+ signaling. This study suggests that CBD pretreatment may resist the effects of METH on DRD1 by competitive binding.